2021
DOI: 10.3390/ijms23010260
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale-Engineered Muscle Constructs: PEG Hydrogel Micro-Patterning on an Electrospun PCL Mat Functionalized with Gold Nanoparticles

Abstract: The development of new, viable, and functional engineered tissue is a complex and challenging task. Skeletal muscle constructs have specific requirements as cells are sensitive to the stiffness, geometry of the materials, and biological micro-environment. The aim of this study was thus to design and characterize a multi-scale scaffold and to evaluate it regarding the differentiation process of C2C12 skeletal myoblasts. The significance of the work lies in the microfabrication of lines of polyethylene glycol, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Such techniques include micropatterning, 3D bioprinting, and electrospinning [263]. Micropatterning techniques such as soft lithography, photolithography, or hot embossing lithography have been used to investigate the effect of different topographies such as grooves, ridges, channels, or posts on cell arrangement and function [264,265]. Charest and colleagues made use of hot embossing lithography to generate different micropatterns, such as grooves, ridges, and holes, with different sizes.…”
Section: Modeling Aging-related Muscle Degenerationmentioning
confidence: 99%
“…Such techniques include micropatterning, 3D bioprinting, and electrospinning [263]. Micropatterning techniques such as soft lithography, photolithography, or hot embossing lithography have been used to investigate the effect of different topographies such as grooves, ridges, channels, or posts on cell arrangement and function [264,265]. Charest and colleagues made use of hot embossing lithography to generate different micropatterns, such as grooves, ridges, and holes, with different sizes.…”
Section: Modeling Aging-related Muscle Degenerationmentioning
confidence: 99%
“…As discussed previously, PEGDA hydrogel has been used for various applications within the field of tissue engineering [ 37 , 209 , 210 ]. In the area of organ-on-chip devices, it has been tested for 3D cell culture platforms such as skeletal muscle microtissues (SMT) [ 211 , 212 , 213 ]. Designing functional in vitro SMT involves two crucial elements: scaffold architecture and functionality.…”
Section: 3d Pegda Hydrogel For Cardiac Tissue Engineeringmentioning
confidence: 99%
“…Beldjilali-Labro et al developed aligned PCL nanofiber via electrospinning with a rotating drum collector and coated with gold nanoparticles (AuNP). [88] AuNP-PCL nanofibers were then micropatterned on PEG hydrogel to facilitate the myogenic differentiation of cultured C2C12 myoblasts. The directional elongation, myotube formation, and expression of characteristic markers (e.g., myf4, IGF-I/II, URB5, and MyHCemb) all indicated that the aligned AuNP-PCL nanofibers on PEG hydrogel promoted the myogenic differentiation.…”
Section: Composite Nanofibersmentioning
confidence: 99%